Corporeal Sounding: Listening to Bomba Dance, Listening to puertorriqueñxs - Power-Sotomayor, Jade (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2020)
Afro-Puerto Rican bomba, the island’s oldest extant genre of drum, dance, and song, is a fundamentally sonic practice. Unique in the tight relation between the execution of movements and the simultaneous sounding of the lead drum, bomba dance enacts a challenge to the Western focus on the visual spectacle of dancing and draws attention to what Ashon Crawley calls the “choreosonic,” or the inextricable linking of movement and sound. Bomba dance attends to creating rhythmic variation through specific movement choices strategically placed within and simultaneously producing the sonic framework of drumming and dancing. As such, it requires a listening that ultimately structures a relationality that interrupts the colonial, white supremacist and heteropatriarchal logic that contains Puerto Rican bodies. Through a close reading of different bomba dancings, this article examines how the dancer’s sounded movements claim, not space itself, but a relation to space and place, pulling bodies into the social and unravelling temporal boundedness. It argues that bomba’s growing popularity on the island and in the diaspora is a measure of its capacity for “listening to flesh,” “listening to flesh speak,” underscoring how this particularly addresses and is attuned to a subaltern, racialized, and femme-identified flesh. As such, bomba is an important case study examining the intersections between sound studies and performance studies, blurring clear distinctions between listening to and doing sound.